Surface structure and properties of hydroxyapatite coatings on NiTi substrates - Marchenko, Ekaterina S.; Dubovikov, Kirill M.; Baigonakova, Gulsharat A.; Gordienko, Ivan I.; Volinsky, Alex A. (Coatings)
Hydroxyapatite coatings were deposited for 1, 2, and 3 h on NiTi substrates using plasmaassisted radio frequency sputtering. The matrix consisted of NiTi B2 and NiTi B19’ phases and Ti2Ni, Ni3Ti, and Ni4Ti3 intermetallic compounds. The surface coating was monoclinic hydroxyapatite. Increasing the deposition time to 3 h made it possible to form a dense hydroxyapatite layer without visible defects. The phase contrast maps showed that the coating consisted of round grains of different fractions, with the smallest grains in the sample deposited for 3 h. The wettability tests showed that the coating deposited for 3 h had the highest surface energy, reflected in the proliferation density of the MCF-7 cell line.